2018
DOI: 10.1016/j.bbrc.2018.05.080
|View full text |Cite
|
Sign up to set email alerts
|

Replacing C189 in the bZIP domain of Zta with S, T, V, or A changes DNA binding specificity to four types of double-stranded DNA

Abstract: Zta is a bZIP transcription factor (TF) in the Epstein-Barr virus that binds unmethylated and methylated DNA sequences. Substitution of cysteine 189 of Zta to serine (Zta(C189S)) results in a virus that is unable to execute the lytic cycle, which was attributed to a change in binding to methylated DNA sequences. To learn more about the role of this position in defining sequence-specific DNA binding, we mutated cysteine 189 to four other amino acids, producing Zta(C189S), Zta(C189T), Zta(C189A), and Zta(C189V) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
(60 reference statements)
1
5
0
Order By: Relevance
“…In contrast to serine, replacing Cys 189 by an alanine or threonine decreased binding affinity for meZRE2 by a factor of 1.6 or 2.3, respectively (Figure 5B ). These results can be rationalized structurally (Figure 5 legend) and are consistent with a recent protein binding microarray study that found reduced meZRE2 binding for ZEBRA mutants C189A and C189T ( 93 ).…”
Section: Resultssupporting
confidence: 89%
“…In contrast to serine, replacing Cys 189 by an alanine or threonine decreased binding affinity for meZRE2 by a factor of 1.6 or 2.3, respectively (Figure 5B ). These results can be rationalized structurally (Figure 5 legend) and are consistent with a recent protein binding microarray study that found reduced meZRE2 binding for ZEBRA mutants C189A and C189T ( 93 ).…”
Section: Resultssupporting
confidence: 89%
“…Protein binding reactions were performed as described previously. 23,36,51,52 Briefly, 180 ng of plasmid containing DNA binding domains was used to express proteins using the PureExpress in vitro transcription translation kit (NEB) in a 25 μL reaction volume following the manufacturer's instructions. The double-stranded arrays and in vitro-expressed proteins were blocked with 4% milk and BSA before the binding reaction.…”
Section: ■ Experimental Proceduresmentioning
confidence: 99%
“…37 At a structural level, this work highlighted an alanine residue in CREB1, cJun, and cFos, a serine residue in Zta, and a valine in CEBPB explaining the altered DNA binding specificity. 37 Mutagenesis experiments that mutated serine 189 in Zta 51 and a conserved valine in CEBPB 52 highlighted the important roles of these residues in determining the specificity of binding to 5mC and 5hmC. In this study, we examined the effects of 5mC, 5hmC, 5fC, and 5caC in one strand of dsDNA on sequence-specific binding of five bZIP domains (CREB1, ATF2, Zta, ATF3|cJun, and cFos| cJun).…”
mentioning
confidence: 99%
“…23 specific DNA binding ability. 26,27 Here, the contribution of 5mC and 5hmC in one strand of dsDNA to NFATc2 binding was examined.…”
Section: Introductionmentioning
confidence: 99%
“…To further explore the range of DNA binding of NFATc2, we performed protein binding microarray (PBM) experiments with microarrays containing three different types of DNA, single-stranded DNA (ssDNA), dsDNA with 5mC in one strand and a cytosine in the second strand (dsDNA­(5mC|C)), and dsDNA with 5hmC in one strand and a cytosine in the second strand (dsDNA­(5hmC|C)), and compared these data to previous data of NFATc2 binding to dsDNA with cytosine in both strands (dsDNA­(C|C)) and where both cytosines in all CG dinucleotides contain 5mC (dsDNA­(5mCG)) . Previously, we have examined several bZIP family TFs binding with these modified dsDNAs and identified the critical roles of conserved amino acids in their sequence-specific DNA binding ability. , Here, the contribution of 5mC and 5hmC in one strand of dsDNA to NFATc2 binding was examined.…”
Section: Introductionmentioning
confidence: 99%